2005
DOI: 10.1097/01.pas.0000152134.36030.b7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Micrometastatic Disease in Melanoma Sentinel Lymph Nodes by Enhanced Pathology

Abstract: Lymphatic mapping and sentinel lymph node (SLN) biopsy are widely used as a staging technique for patients with cutaneous malignant melanoma who are at risk for metastases. SLN status has been shown to be a strong predictor of prognosis, and a variety of techniques have been used to identify minimal metastatic disease in SLNs. However, there is no validated consensus method for the optimal histologic analysis of SLNs harvested from melanoma patients. This study was conducted: 1) to assess the yield of metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(102 citation statements)
references
References 57 publications
2
98
0
2
Order By: Relevance
“…In routine pathologic analysis of melanoma with a median thickness of 3.0 mm, Spanknebel et al found that 20% of the patients were SN positive, [22]. However, after enhanced patholocic analysis 61% of the patients had positive SN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In routine pathologic analysis of melanoma with a median thickness of 3.0 mm, Spanknebel et al found that 20% of the patients were SN positive, [22]. However, after enhanced patholocic analysis 61% of the patients had positive SN.…”
Section: Discussionmentioning
confidence: 99%
“…Both Berk et al and Rutkowski et al used serial sectioning in their pathologic analysis of the SN. Spanknebel et al reports that if ''routine'' pathologic analysis is used instead of enhanced pathologic analysis up to 12% of positive SN are reported as negative [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Thus in melanoma SLNs, whereas protocols sampling only 1 central step will detect metastases in approximately 16% of patients, 6 studies using more extensive sampling have reported metastasis detection rates varying between 28% and 61%. 8,9,[29][30][31] This variation in metastasis detection rates may not only be caused by different sampling protocols, but also by different primary tumor characteristics (particularly the mean tumor thickness) and most likely also by differences in the definition of benign nevus inclusions in the various studies. The additional value of increased step-sectioning has been a matter of debate, as workload constraints have been weighed against the varying number of additional metastases detected.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Since the inception of the sentinel lymph node biopsy procedure, significant strides have been made both in refining the surgical approach to nodal identification and excision and in defining the optimal method of examination of the harvested tissue in the pathology laboratory. 5,6 Histological evaluation using both routine stains and immunohistochemistry is the practise in most laboratories. Molecular detection of melanocytespecific mRNA by reverse transcription polymerase chain reaction (RT-PCR) is also applied to sentinel lymph node evaluation in many centres.…”
Section: Introductionmentioning
confidence: 99%